Unveiling Determinants in Rice Supply Chain Studies: A Bibliometric Analysis on Food Security - Aziz, Tengku Nurul Aishah Tengku; Nordin, Norani; Ismail, Haikal (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This paper seeks to provide an overview of the characteristics of the Rice Supply Chain (RSC) as studied across various research areas related to food security concerns. In agriculture, Rice Self-Sufficiency (RSS) level is an indicator of food security. However, food security encompasses broader factors such as availability, accessibility, stability, and utilisation. Given that rice holds significant importance as one of the world's staple foods, addressing the increasing demand for rice is seen as a crucial strategy to enhance national resilience against food insecurity. Inefficiencies in the rice supply chain can negatively impact production, storage, and distribution, consequently diminishing the RSS. In line with the growing attention to food security, there is a need to better understand the importance of sustaining the production of rice to cater to food security issues within broader academic research. Thus, this study has two main objectives: 1) to examine the characteristics and development of literature related to the RSC and, 2) to identify the thematic areas related to the RSC research and their connections to specific disciplines. To achieve this, a Systematic Literature Review (SLR) and bibliometric analysis of 165 journal articles listed in the Web of Science (WoS) and SCOPUS databases was conducted. This analysis revealed significant findings in research activity, highlighting the extensive and multidisciplinary nature of the studies. Study results indicate a gap in relational bibliometric studies within the field of RSC. Nevertheless, there is still potential for increased collaboration across disciplines and further investigation into how diverse RSC studies touch on food security issues for future reference.